Globalization and the growth of transnational crime - Nelken, David (Henry Stewart Talks, 2008)
Types of organized criminals, Types of organized crimes, Methods for tackling the challenges they pose, The changing context of these phenomena, Connections between globalization, transnational crime and crime control, Consider the larger conditions in which such policing takes place
Archived at 2022/04/03